Quality of service (QoS) based service retrieval engine - Dong, Hai; Hussain, Farookh Khadeer; Chang, Elizabeth (Association for Computing Machinery (ACM), 2008)
It is observed that there are few service evaluation and ranking methodologies currently available in the SOE. In this paper, we propose an innovative service evaluation and ranking strategy, based on the measurement of trustworthiness and reputation of services (or service providers). CCCI Metrics originally proposed and developed by Chang et al [1] is used to measure the trustworthiness and reputation of e-services. Here we extend the application of CCCI Metrics to the field of service retrieval. A java-based search engine prototype is designed, with the purpose of implementing the trustworthiness and reputation-based service search, evaluation and ranking. Conclusions and future works are drawn in the final section.